Sobre alguns contrastos fonològics en l'entonació del català - Prieto, Pilar; Vanrell, Maria del Mar (Caplletra. Revista Internacional de Filologia, 2006)
The main goal of this article is to provide evidence in favor of the phonological character of some intonational contrasts in Catalan. First, the article shows that tonal alignment differences with respect to metrically strong positions are crucial for the distinction between a yes-no question and a wh-question (cf. "¿Que l’ha llogada?" vs. "¿Qui l’ha llogada?") and between a command and a request ("¡Vine!" vs. "¡Vine!") in Central Catalan. Second, the article reports the major results from the application of the Categorical Perception Paradigm to a pitch height contrast in Majorcan Catalan(Vanrell 2006a). Experimental resuls show that a small variation in the pitch height of the pretonic syllable is an important perceptual cue in distinguishing yes-no questions from wh-questions in this dialect ("¿Que l’hi duries?" vs. "¿Què li duries?"). The Catalan data demonstrate that small phonetic changes in pitch alignment and pitch scaling can becrucial in the perception of intonation contours. Crucially, the data call for a revision of the autosegmental-metrical (AM) model of intonation: while the AM model predicts that differences in tonal alignment have the potential of creating phonological contrasts, it does not allow for phonological differences in pitch range.